Impact of Highly Active Anti-Retroviral Therapy on paediatric Human Immuno-Deficiency Virus associated left ventricular dysfunction within the Johannesburg teaching hospital complex - Pepeta, Lungile (My University, 2012)
Cardiovascular disease is a common complication of advanced HIV disease in both paediatric and adult patient groups and may present with left ventricular (LV) dysfunction. Introduction of Highly Active Antiretroviral Therapy (HAART) has improved outcomes in patients presenting with LV dysfunction. However, mitochondrial toxicity, a complication of HAART, may present with myocardial dysfunction.
Research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree MASTER OF MEDICINE (MMED.) (PAEDIATRICS AND CHILD HEALTH). Department of Paediatrics and Child Health Johannesburg, South Africa, 2012
Keywords: Antiretroviral Therapy, Highly Active